Lipid Messenger Phosphatidylinositol-4,5-Bisphosphate Is Increased by Both PPARα Activators and Inhibitors: Relevance for Intestinal Cell Differentiation - Katerina Cizkova; Katerina Koubova; Zdenek Tauber (Biology, 2022)
We investigated the effects of PPARα activators fenofibrate and WY-14643 as well as the PPARα inhibitor GW6471 on the PI3K/Akt/PTEN pathway of intestinal cell differentiation. Our previous study showed that all these compounds increased the expression of villin, a specific marker of intestinal cell differentiation in HT-29 and Caco2 cells. Our current results confirmed the central role of lipid messenger phosphatidylinositol-4,5-bisphosphate (PIP2), a known player in brush border formation, in mediating the effects of tested PPARα ligands. Although all tested compounds increased its levels, surprisingly, each of them affected different PIP2-metabolizing enzymes, especially the levels of PIP5K1C and PTEN. Moreover, we found a positive relationship between the expression of PPARα itself and PIP2 as well as PIP5K1C. By contrast, PPARα was negatively correlated with PTEN. However, the expression of antigens of interest was independent of PPARα subcellular localization, suggesting that it is not directly involved in their regulation. In colorectal carcinoma tissues we found a decrease in PTEN expression, which was accompanied by a change in its subcellular localization. This change was also observed for the regulatory subunit of PI3K. Taken together, our data revealed that fenofibrate, WY-14643, and GW6471 affected different members of the PI3K/Akt/PTEN pathway. However, these effects were PPARα-independent.